The other evangelicals: a story of liberal, Black, progressive, feminist, and gay Christians, and the movement that pushed them out - Sharp, Isaac B. (William B. Eerdmans Publishing Company, 2023)
"An alternative reading of twentieth-century evangelical history that recovers the stories of some of evangelicalism's least known groups, long neglected movements, and widely overlooked figures"--